Peran Literasi Digital dalam Projek Penguatan Profil Pelajar Pancasila di Sekolah Dasar Negeri Gurawan - Janti, Janti Murdiani; Wijayanti, Ratih Kumala; Markhamah, Markhamah; Sutama, Sutama (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
Digital literacy is an important competency in supporting the success of the Pancasila Student Profile Strengthening Project (P5). This study aims to describe the role of digital literacy in the implementation of P5 at SD Negeri Gurawan. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that digital literacy plays a role in improving critical and creative thinking skills, supporting collaboration, instilling digital ethics, encouraging learning independence, and strengthening understanding of local and global cultures. In addition, the use of digital media facilitates students in expressing ideas and works, which has an impact on strengthening the six dimensions of the Pancasila Student Profile. These findings indicate that digital literacy not only improves the quality of learning, but also shapes student character according to Pancasila values.